Enhancing the leaching performance of molybdenite and Co-white alloy simultaneously: A structure conversion process. (15th May 2022) - Zhang, Dingchuan; Sun, Fenglong; Zhao, Zhongwei; Liu, Xuheng; Chen, Xingyu
Graphical abstract: Highlights: A conversion method is proposed for enhancing the leaching of MoS2 and Co-white alloy. Conversion product with high leaching activity was prepared by the method. The product can be completely decomposed using moderate leaching conditions. The decomposition of Mo and Co is about 99% without using catalysts. Sulfur of ternary sulfides is oxidized to elemental sulfur in the residues. Abstract: Molybdenite (MoS2 ), driven by its unique sandwich structure, is chemical inert and hydrophobic leading to a high refractory sulfide ore, and Co-white alloy, due to its grinding and corrosion resistance, is a refractory product (mainly containing Co, Fe, Cu and Si) for use in traditional hydro-metallurgical processing. In this work, a novel, two-step process was proposed to enhance the leaching performance of both molybdenite and Co-white alloy. First, prior to leaching and based on the sulfur affinity of Co, Fe and Cu, molybdenite and Co-white alloy were converted into ternary sulphides (Mx Mo6 S8 ) with high leaching activity. Second, a leaching process was carried out in an autoclave with oxygen as the oxidant. Compared to molybdenite and Co-white alloy, the leaching performance of the ternary sulfides was greatly improved under moderate conditions. During the leaching of ternary sulfides, the sulfur is partially converted to elemental sulfur, which is unlike the acid leaching process of molybdenite where sulfur is oxidized to sulfuric acid. Factors affecting the decomposition of ternary sulfide were also studied in detail under moderate conditions. The optimal leaching conditions were found to be a temperature of 120 °C, a sulfuric acid concentration of 1 mol/L, a duration of 150 min, and an oxygen partial pressure of 0.95 MPa. The oxidation efficiency of molybdenum reached 99%, the elemental sulfur yield was 55%, and the leaching efficiencies of cobalt and copper were both greater than 99%.